How do digital inclusion and energy security risks affect mineral resources trade? Evidence from world-leading mineral trading countries - Sohail M.T.; Din N.M. (Elsevier Ltd, 2025)
Mineral resources play a vital role in the development of renewable energy investment. Therefore, studying the factors that can influence the mineral resources trade is crucial in increasing the pace of global efforts toward energy transition. The conventional environment of natural resource trading is going through substantial changes in an age characterized by quick technology breakthroughs and increased dependence on digital finance systems. In addition, countries' policies and plans are now heavily influenced by the quest for energy security. However, whether digital inclusion and energy security risks have any role in boosting mineral resources trade is an empirical question overlooked by past studies. The current analysis fills the gap by investigating the influence of digital inclusion and energy security risks on mineral resources trade in world-leading mineral trading countries by utilizing 2SLS and GMM methods for the period from 2007 to 2022. The findings indicate that mineral trade is favorably influenced by digital finance and related variables such as ATMs, bank branches, debit cards, and electronic payments. While ICT has beneficial effects on the expansion of trade in mineral resources. Likewise, energy security risks proliferate the trade in mineral resources. Additionally, GDP and foreign direct investment positively contribute to the trade in mineral resources. In contrast, the consumer price index hurts mineral resources trade. Thus, governments can establish a more robust, fair, and ecologically sustainable global natural resources trading landscape by coordinating policies to take advantage of the favorable synergies between digital finance and energy security issues. ? 2023 Elsevier Ltd